Investment determinants at the firm-level: The case of Portuguese industrial SMEs - Luís Pacheco (International Journal of Business Science & Applied Management (IJBSAM), 2017)
The objective of this paper is to empirically determine the investment determinants at the firm level. Many empirical papers studied the investment determinants from a macroeconomic point of view but the analysis of the main investment determinants from an internal point of view has been less studied. This paper fills that gap, particularly for the case of Portugal, focusing on industrial SMEs. Using a panel data methodology and considering an unbalanced sample of 2456 Portuguese manufacturing SMEs for the period 2011-2015 our results indicate that SMEs with higher profitability, debt and liquidity and of smaller size tend to present higher levels of investment. This exploratory paper gives a contribution to clarify which are the main internal determinants of firms' investment, which is an important issue not only for managers but for all the stakeholders, particularly the policymakers.
Keywords: 650; investment determinants; Small and medium enterprises; Panel-data methodology; Investment decisions; Portugal